A review of current treatment strategies for gestational diabetes mellitus - Kristi W Kelley; Dana G Carroll; Allison Meyer (BioExcel Publishing Ltd, 2015)
Approximately 90% of diabetes cases in pregnant women are considered gestational diabetes mellitus (GDM). It is well known that uncontrolled glucose results in poor pregnancy outcomes in both the mother and fetus. Worldwide there are many guidelines with recommendations for appropriate management strategies for GDM once lifestyle modifications have been instituted and failed to achieve control. The efficacy and particularly the safety of other treatment modalities for GDM has been the source of much debate in recent years. Studies that have demonstrated the safety and efficacy of both glyburide and metformin in the management of patients with GDM will be reviewed. There is a lack of evidence with other oral and injectable non-insulin agents to control blood glucose in GDM. The role of insulin will be discussed, with emphasis on insulin analogs. Ideal patient characteristics for each treatment modality will be reviewed. In addition, recommendations for postpartum screening of patients will be described as well as recommendations for use of agents to manage subsequent type 2 diabetes in patients who are breastfeeding.